2018
DOI: 10.1029/2017jd027927
|View full text |Cite
|
Sign up to set email alerts
|

Satellite‐Observed Impacts of Wildfires on Regional Atmosphere Composition and the Shortwave Radiative Forcing: A Multiple Case Study

Abstract: Emissions of aerosols and trace gases from wildfires and their direct shortwave radiative forcing (DSRF) at the top of atmosphere were studied using satellite observations from Moderate-Resolution Imaging Spectroradiometer, Atmospheric Infrared Sounder, Clouds and Earth Radiant Energy System on Aqua, and Ozone Monitoring Instrument on Aura. The dominant fuel types of the selected fire cases in the northeast of China (NEC), Siberia (Russia), and California (USA) are cropland, mixed forest, and needle-leaf fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…There is exhaustive literature estimating smoke emission coefficients of total particulate matter, ,,,, whereas the values reported herein are the first for many trace gas species. There is only one instance of a satellite-derived HCHO α value for a similar fuel type (0.56 g MJ –1 ) that compares well to these results (0.46 g MJ –1 ). The NO 2 (0.28 g MJ –1 ) value and range of NO x (0.24–1.2 g MJ –1 ) ,, derived using satellite observations are higher than the NO 2 (0.18 g MJ –1 ) value estimated here.…”
Section: Results: Speciated Emissionssupporting
confidence: 72%
“…There is exhaustive literature estimating smoke emission coefficients of total particulate matter, ,,,, whereas the values reported herein are the first for many trace gas species. There is only one instance of a satellite-derived HCHO α value for a similar fuel type (0.56 g MJ –1 ) that compares well to these results (0.46 g MJ –1 ). The NO 2 (0.28 g MJ –1 ) value and range of NO x (0.24–1.2 g MJ –1 ) ,, derived using satellite observations are higher than the NO 2 (0.18 g MJ –1 ) value estimated here.…”
Section: Results: Speciated Emissionssupporting
confidence: 72%
“…Thus, forest fires and agricultural burning in this region are two important sources of emission [44,45]. Severe air pollution due to long-distance transportation of smoke pollution was documented [46,47], and modern records reveal large forest fires in the region such as in 1987 [48], 2004, and 2006 [18].…”
Section: Study Areamentioning
confidence: 99%
“…Studies have pointed out biomass burning is the reason that elevates Amazon HCHO concentration in dry seasons (Kesselmeier et al, 2002;Kim et al, 2011). Based on measurements in laboratorial experiments (Karl et al, 2007;Stockwell et al, 2014) and retrievals using satellite observations (Fu et al, 2018), large variations are found in the emission factors of HCHO and VOCs from fires (Akagi et al, 2011). However, the distribution of fire and the strength and mode of fire can be distinct from case to case.…”
Section: 1029/2019ea000627mentioning
confidence: 99%
“…Satellite observations show the global distribution of HCHO and other trace gases such as NO 2 are coherent with the fire distribution. Examples are seen in South America, Africa, and Northeastern Asia (Fu et al, 2018;Marbach et al, 2005Marbach et al, , 2008. Studies have pointed out biomass burning is the reason that elevates Amazon HCHO concentration in dry seasons (Kesselmeier et al, 2002;Kim et al, 2011).…”
Section: 1029/2019ea000627mentioning
confidence: 99%
See 1 more Smart Citation